2018
DOI: 10.1017/age.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Tenure and Property Rights on Farm Households’ Willingness to Accept Incentives to Invest in Measures to Combat Land Degradation in Nigeria

Abstract: Influence of land tenure and property rights (LTPRs) on farmers’ willingness to accept (WTA) incentives to embrace climate-smart agriculture (CSA) to combat land degradation was examined with choice experiment data collected from 1,138 farmers drawn across 16 States in Nigeria. Data analysis within random-effect and mixed logit framework revealed the existence of strong linkages between the payment vehicle, LTPRs and farmers’ CSA preferences. While farmers who were dependent on leased and/or communal lands exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
(47 reference statements)
6
31
0
Order By: Relevance
“…Unless land restoration activities are accompanied by measures to expand access to alternative energy sources, replanting forests, shrublands and woodlands will have only a short-term and limited effect. Long-term investments in land restoration activities are often hindered by lack of clearly de ned and legally enforceable land property rights and land tenure security 17,18 . It is in all likelihood not possible to restore all degraded lands in the Sahel by government actions or donor-funded projects.…”
Section: Discussionmentioning
confidence: 99%
“…Unless land restoration activities are accompanied by measures to expand access to alternative energy sources, replanting forests, shrublands and woodlands will have only a short-term and limited effect. Long-term investments in land restoration activities are often hindered by lack of clearly de ned and legally enforceable land property rights and land tenure security 17,18 . It is in all likelihood not possible to restore all degraded lands in the Sahel by government actions or donor-funded projects.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling process was based on the nationwide Agricultural Development Program (ADP) structure that split each state into zones, blocks and cells for easy administration and extension outreach. As outlined by Shittu et al (2018), cells are groups of close farming communities assigned to an Agricultural Extension Officer, while blocks are groups of five to eight cells under the supervision of a block extension supervisor. A number of blocks form a zone and each state in Nigeria has about three or four agricultural zones.…”
Section: Data and Sampling Proceduresmentioning
confidence: 99%
“…It aims to "sustainably increase agricultural productivity and incomes, build resilience and capacity of agricultural and food systems to adapt to climate change, and reduce or remove greenhouse gases while enhancing national food security" (Neufeldt et al 2013). However, despite the conceptual promise and attractiveness of CSA, empirical evidence of its success under Africa's diverse agroecologies and socioeconomic conditions are observed to still be scanty and mixed in terms of results (Neate 2013;Shittu et al 2018). For instance, while Brüssow et al (2015) report that implementing a climate-smart approach contributes to improved food security in Tanzania, Asfaw et al (2016) reported no significant impact of these practices on crop outcomes in Niger.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with precarious hold on the land, such as women and strangers, are particularly constrained to make such investments. Thus, World Bank [34] reported that while farmers in Nigeria who were dependent on leased and/or communal lands expressed implicit dislike for climate-smart agriculture (CSA)-related investments, the majority with freehold titles, particularly those with registered titles, expressed positive willingness-to-accept incentives to embrace CSA and combat land degradation [35].…”
Section: Economics Of Adaptation To Climate Change In the Agriculturementioning
confidence: 99%